Science in Decline: An In-depth Analysis of Factors Responsible for the Diminished Interest in Secondary and Higher Secondary Levels in Bangladesh - Chowdhury, Younus; Islam, Muhammad Monirul; Rabbi, Md. Fajlay (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2024)
The significance of science education has reached a pinnacle in human history at the era of the fourth industrial revolution. Regretfully, the younger generation in Bangladesh has shown a diminishing interest in science education during the past 20 years. This study investigated the barriers to science education that secondary and upper school students face. The association between enrollment and several independent variables that affect students' interest in science education was investigated using a quantitative approach. Using a Likert scale technique, data was gathered from students at three distinct educational institutions. The investigation revealed that factors that statistically significantly influence interest in science education were personal preference, costs associated with the subject, career opportunities, and the classroom setting. To address this problem, the report offered suggestions to educators, leaders in education, and politicians.